AN INNOVATIVE APPROACH IN EDUCATION - Brezin, Veselin; Zhelyazova, Boyanka; Milchev, Radoslav; Mladenova, Marina; Tsvetkova, Elena (Innovation in Woodworking Industry and Engineering design, 2013)
Strengthening the links between education systems, in order to develop the potential of young people is at the core of European cooperation process. Leading institutions are there to introduce and provide better teaching and learning through use of new information and communication technologies (ICT). One of the priority areas of the Strategic framework for education and training („ET 2020“) is to promote and develop creativity and innovation through new instruments, which use modern ICT and by training teachers to use ICT. Information and communication technologies provide a variety of methods and tools that open up new opportunities in distance learning students from the University of Forestry. They allow supporting the educational process by organizing it in a way, that takes into account the individual needs of students and allow building up of important digital competencies needed to achieve "knowledge-based" economy.